Effects of a Peganum harmala (Zygophyllaceae) preparation for root canal disinfection. (24th January 2018) - Tabrizizadeh, Mehdi; Kazemipoor, Mahnaz; Hakimian, Mahdi; Maleksabet, Mojdeh; Kazemipoor, Maryam; Zandi, Hengameh; Pourrajab, Fatemeh; Che, Chun‐tao; Cordell, Geoffrey A.
Abstract : The aim of this study was to determine the antimicrobial capacity, minimum inhibitory concentration (MIC), and cytotoxic effects of a Peganum harmala seed extract in comparison to 5.25% sodium hypochlorite (NaOCl). The oral pathogen Enterococcus faecalis was used to evaluate the antimicrobial capacity, and the MIC values were determined through serial dilution. Inhibition zones were measured in millimeter, and the data were analyzed statistically by analysis of variance and the Tukey HSD test. For cytotoxicity testing, P. harmala seed extract and 5.25% NaOCl solution were incubated with L929 fibroblast cells. After 1, 24, and 72 hr of incubation, cells were stained and the optical density determined with an enzyme‐linked immunosorbent assay (ELISA) reader. Data were analyzed with Chi‐Square statistical test. The significance level was set at p <  .05. There was no significant difference between the antimicrobial capacity of 5.25% NaOCl and the P. harmala extract ( p  > .05; MIC 4 μg/ml). The Microculture Tetrazolium (MTT) assay test showed that the cytotoxic effects of the P. harmala extract were significantly lower than 5.25% NaOCl ( p  < .05). The results show that 5.25% NaOCl and P. harmala seed extract have similar antimicrobial activity against Enterococcus faecalis ; but P. harmala, which shows reduced cytotoxicity, should be considered for further investigation as a safe, phytotherapeutic, intracanal irrigant.